Seasonal variation of dry and wet islands in Beijing considering urban artificial water dissipation - Zhuoran Luo (Nature Portfolio, 2021)
Abstract Urbanization has resulted in dry/wet island effects in built-up areas. Compared to the limited number of observational datasets, simulations can provide data with richer spatial distribution, thereby proving to be more helpful for revealing the spatial distribution of dry/wet islands. This study simulated dry/wet island effects during typical summer and winter conditions in Beijing by coupling the Artificial Water Dissipation Urban Canopy Model with the Weather Research and Forecasting model. Observations of relative humidity, absolute humidity, and temperature from weather stations in Beijing were used to verify the model. The results showed that in 2020, Beijing was prone to be a dry island during summer, with the relative humidity approximately 5–10% lower than the surrounding suburbs. The dry island effect was not obvious in winter, and Beijing tended to be a wet island. The influence of artificial water dissipation on dry/wet islands is higher in winter than in summer. By considering the water vapor from artificial water dissipation, humidity in urban areas can be simulated more accurately.